A comparative study of Iraqi crude oil taken from the Nasiriyah refinery with various local and global crude oils. - T. Khathi, Mohammed; A. Ali Al-Yasiri, Ali (University of Thi-Qar Journal of Science, 2019)
In the present work, was evaluated and compared some physicochemical properties of crude oil which is obtained from Nasiriyah refinery in south of Iraq with some physicochemical properties of various local and global of crude oils. Many methods were used in this study to evaluate some chemical content as sodium ,potassium ,calcium, magnesium, vanadium,Iron, copper, lead and nickel in samples of Iraqi Oil in Nasiriya Refinery , as well as some physical properties included color , density, Ash content wt%, carbon residue wt% , water, salt , Sulfur content % wt, Heat of combustion Kcal/Kg , Thermal conductivity, Specific heat and Latent heat of vaporization were determinate . Also in this study viscosity were measured with different temperatures to observe the effect of temperature on oil viscosity. Range concentration of metals can be cleared by the series Ca > Na > Mg> V > Ni > K > Fe> Pb > Cu. The present study has shown that high levels of metals ions in oil refinery whereas the physical properties were closed to previous findings conducted on a crude oil in Iraq and other countries. The study recommended to possible using of high levels of heavy metals in oil in scientific and industrial purposes as well as removal these metals contribute in reducing of contaminations problems.